Residential Mobility and Changes in Deprivation Levels For 0 – 4 Year Olds in New Zealand - Robertson, Oliver; Nathan, Kim; Howden-Chapman, Philippa; Baker, Michael; Carr, Polly Atatoa; Pierse, Nevil (International Journal of Population Data Science, 2020)
Introduction High residential mobility has been shown to have a negative impact on young children, with long-term consequences for their physical and mental health, and social outcomes. Understanding the broad trends in moves and differentiating between moves to neighbourhoods which are likely to have ‘positive’ or ‘negative’ consequences is an important question in the residential mobility literature, with important implications for public policy and children’s health. Objectives and Approach The aims of this study are to describe the level and changes in neighbourhood deprivation that occur during residential moves involving children aged 0–4 years of age in New Zealand, and to assess whether these changes differ for children of different ethnicities. Our cohort is 565,689 children born in New Zealand from 2004 to 2018. The dataset of residential moves is created using the full address notification table from the Integrated Data Infrastructure, a set of government data tables that have been linked and anonymised by Statistics New Zealand. Results While there is a reasonable amount of mobility in terms of the deprivation of the area in which a child lives, the most likely outcome of a move is that it will be to an area with the same level of deprivation. This is especially true for the most and least deprived areas. Areas of high deprivation have the highest levels of churn and residential mobility. Māori and Pasifika children have lower levels of socioeconomic mobility and are more likely to move into and to stay in, areas of high deprivation. Conclusion / Implications Children living in highly deprived areas are likely to stay in high deprivation areas. Children living in these areas also move more frequently than the general population. Māori and Pasifika children are overrepresented in high deprivation areas, and on average they move more frequently than the group of all children aged 0 – 4.